Prioritization of master data domains in public sector organisations - Haneem, Faizura; Kama, Nazri; Azmi, Azri; Azizan, Azizul; Mohd Sam, Suriani (2016)
The Master Data Management (MDM) establishment in public sector transforms the government efficiency by encouraging the resource sharing, data collaboration and citizen-centeredness. Nevertheless, defining and prioritizing master data domains across organisations as an essence of implementing MDM is a very challenging process. Although customer, product, locations, finance and employee data domains have been among the most targeted master data domains where MDM initiatives are focused on, yet the prioritization of these domains is very critical for better planning of the MDM implementation. Less attention is given in the existing literatures which focusing in this research area.Hence, this paper aims to clarify master data domains and its prioritization in public sector organisations using qualitative and quantitative approach. It involves participative case studies from nine Malaysia’s public sector organisations and experts’ opinion to define the master data domain and its prioritization in Malaysia’s public sector organisations. The result of this study identified master data domains in the public sector generally grouped into three domains; 1) service providers, 2) services and products, and 3) customers’ profile.The highest priority of the master data domain in the public sector is services and product and followed by the customer’s profile and service provider domain. From an academic perspective, this paper represents a clarification of master data domains and its prioritization in public sector organisations within the area of MDM. In addition, the paper can serve Malaysia’s Public Sector and other practitioners as a reference in defining and prioritizing the master data domains in order to establish an effective MDM.